Effects of different flowering stages on secondary metabolites in Bletilla striata flowers analyzed by GC-MS and LC-MS - Yang, Lin; Han, Xue; Liu, Hai; Chen, Yaya; Wu, Mingkai; Tan, Longyan (Frontiers in Ecology and Evolution, 2025)
Bletilla striata, a precious traditional Chinese medicinal herb, has long lacked systematic investigation into the dynamic patterns of secondary metabolites in its flowers and their resource utilization potential. This study employed gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS) to comprehensively analyze the spatiotemporal distribution and regulatory mechanisms of secondary metabolites in buds (B) and flowers (F) of the geo-authentic cultivar B.striata ‘Gui Ji 1’ across four critical developmental stages (P1-P4). Volatile components were dominated by esters (e.g., ethyl acetate and ethyl propionate), with peak diversity (81 types) observed at the P3 stage, where total ester content in flowers significantly exceeded that in buds (ethyl acetate in P3-F reached 357.76 mg/g). Non-volatile components prominently featured glycosides like Militarine, Dactylorhin E and organic acids, with P3-stage floral organs exhibiting maximal accumulation of bioactive compounds (Militarine: 37.28 mg/g in P3-F; total polysaccharides: 115.58 mg/g; total flavonoids: 26.56 mg/g in P3-B). Principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) demonstrated that P3-stage flowers (P3-F), enriched with both high-value bioactive components and characteristic aromatic compounds, represent the optimal harvest window for medicinal and fragrance product development, while buds (P3-B) serve as supplementary sources for flavonoid-derived functional ingredients. This study pioneers the construction of a metabolic dynamic atlas for B.striata flowers, revealing coordinated regulatory mechanisms between floral organ development and secondary metabolite accumulation. By shifting focus from traditional rhizome-centric research to floral metabolic profiling, it provides scientific foundations for holistic industrial chain development, precision harvesting strategies, and high-value product design. This study provides a scientific foundation for understanding the dynamic changes of key metabolites, thereby optimizing the harvesting time of B.striata flowers. The findings suggest that the bud stage represents the optimal period for extracting medicinal components.